Corruption and economic order - Volejníková Jolana (Univerzita Pardubice, 2009)
The aim of this article is to refer to problems of corruption from different perspective than the corruption is in most of cases presented. It is concerned about corruption in different economics conditions. Discussion is about forms and methods of corruption in hybrid economies, central planned economies and in situation of transitive economies.
Keywords: Corruption; economic order; hybrid economies; central planned economies; transitive economies